Consumer Protection for Intercity Bus Passengers in Pematangsiantar Against Overloading Practices (An Analytical Study of the Sadd Adz-Dzari'ah Principle) - Isro Ayu Marbun; Zulkifli Nas (LP2M IAIN Palopo, 2026)
The phenomenon of overloading on intercity buses remains common and poses a potential threat to passenger safety. This condition indicates that consumer protection in the transportation sector has not been implemented optimally. Therefore, it is necessary to examine this issue from both the perspectives of positive law and Islamic law, particularly through the principle of Sadd Adz-Dzari'ah as a preventive measure against potential harm. This study aims to examine how overloading practices occur on intercity buses in Pematangsiantar, how legal protection is provided for passengers affected by such practices, and how these practices are analyzed from the perspective of Islamic law through the principle of Sadd Adz-Dzari'ah as a means of preventing harm to consumers. This study employed a non-doctrinal (empirical juridical) research method using the statute approach and conceptual approach, with qualitative data analysis. The findings indicate that the practice of overloading passengers on intercity buses continues to occur frequently, particularly during peak travel periods. This condition not only causes discomfort to passengers but also increases the risk to their safety. Furthermore, legal protection for passengers subjected to such practices has not been implemented effectively, as reflected in weak regulatory supervision, low awareness among business operators, and the limited efforts of passengers to assert their rights. From the perspective of Islamic law, the practice of overloading clearly contradicts the principle of Sadd Adz-Dzari'ah because it creates opportunities for greater harm. Therefore, such practices should be prevented from the outset as a means of protecting the safety and welfare of passengers.